Upper Mantle Seismic Structure of Alaska From Rayleigh and S Wave Tomography. Issue 19 (10th October 2018) - Jiang, Chengxin; Schmandt, Brandon; Ward, Kevin M.; Lin, Fan‐Chi; Worthington, Lindsay L.
Abstract: Mantle shear velocity (Vs) structure beneath the Transportable Array (TA) in Alaska and northwestern Canada is imaged by joint inversion of Rayleigh wave dispersion and teleseismic S  wave travel times. The study connects previously unsampled parts of northern and western Alaska with portions of southern Alaska imaged with earlier seismic arrays. The new Vs tomography shows contrasting lithospheric structure in the plate interior with lower Vs shallow upper mantle indicative of thinner thermal lithosphere south of the Brooks Range and along the transform margin. Higher Vs down to ~200 km beneath the Brooks Range and northern coast is consistent with the presence of a cold stable lithospheric root that may help guide intraplate deformation to the south. In the subduction‐to‐transform transition, a potential slab fragment is imaged beneath the Wrangell volcanic field where modern subduction has slowed due to the thick buoyant crust of the Yakutat terrane. Plain Language Summary: We use a groundbreaking seismic data set from the EarthScope project to investigate the structure of the upper mantle beneath Alaska and northwestern Canada to better understand the effects of ongoing subduction and distinctive blocks within the continental lithosphere. Measurements of seismic body and surface waves are used to construct seismic images from the surface down to 800‐km depth. The images reveal cold thick blocks beneath northern Alaska and the Yukon Territory adjacent to warmer thinner blocks beneath younger geologic provinces to the south, suggesting that cold strong lithosphere in the north helps guide the extent of intraplate deformation driven by the southern plate boundary. The model also identifies a potential slab fragment beneath the Wrangell volcanic field, suggesting slab contributions to volcanic activity and a growing slab tear. Key Points: Upper mantle Rayleigh and S wave tomography using the full Transportable Array in Alaska Thick high Vs lithosphere is found beneath the western Brooks Range and Arctic coast A high Vs potential slab fragment is identified beneath the Wrangell volcanic field